PENGARUH KOMUNIKASI TERAPEUTIK TERHADAP TINGKAT KECEMASAN IBU DALAM MENGHADAPI PROSES PERSALINAN KALA I - Moh Wildan; Jenie Palupi; Sukartini - (Jurnal Penelitian Kesehatan SUARA FORIKES, 2016)
Background: Most pregnant mother experienced the feeling of anxiety prior to the delevires of their babies. This pre-labour anxiety requires a serious attention from the health professionals involved in helping the labour process, including the midwife, because it potentially increases into a higher degree of anxiety when no immediate action is taken to overcome it. The objective of this research was to obtain in depth information on the difference to degree of anxiety which was experienced by pregnant mother prior and post to obtaining therapeutic communications. Methods: This Research used “one group pre test-post design” with total responden of 30 expecting mather admitted to Elisabeth Hospital, Situbondo. The data obtained were then analized using Chi Square statistical tes on 5 % level significance and degree of freedom 4. Results: The result showed that the value of the computed Chi Square X2 (10,582) is higher than that of the stsndard value of X2 presented in Chi Square tables (9,488). Therefore te hypotesis which said that there was a difference degree of anxiety experienced by pregnant mother prior and post to obtaining therapeutic communications was accepted. The value of the contingency coefficience was only 0,392, hence there was a positive correlation, even thought it was no so strong. Conclusion: It could be concluded that the degree of anxiety experienced by pregnant mother facing labour process at term I decreased upon obtaining therapeutic communications from the midwife. Keywords: Therapeutic communications, anxiety, labour